IMPROVEMENT OF SOFT CLAYS BY END BEARING STONE COLUMNS ENCASED WITH GEOGRIDS - Mohammed Y. Fattah (Diyala Journal of Engineering Sciences, 2010)
In this paper, the finite element method is utilized as a tool for carrying out different analyses of stone column–soil systems under different conditions. A trial is made to improve the behaviour of stone column by encasing the stone column by geogrid as reinforcement material.